Combined Lateral and Longitudinal Control for Vehicle Platooning - Miguel Marques Macedo (2021)
The ever increasing demand for mobility in transport networks in recent years has led to a near saturation of road infrastructure in some regions of the world. Conventional approaches to this problem, such as improved road capacity, are no longer viable as they no longer keep up with the necessary vehicle throughput required. Combined with environmental concerns and the desire to minimize the risk of accidents, there is a need for new generation transport methods that aim to solve the problems aforementioned. One possible solution, which has been extensively studied in literature, is vehicle platooning. Vehicle platooning is considered a type of automated cooperative driving where a string of vehicles is driving in close proximity and are interconnected between each other through V2V or V2X links. As a result, vehicle platoons enable a higher road throughput, while reducing fuel consumption, greenhouse gas emissions. In addition to this, they have been found to be much safer for passengers and prevent ghost traffic jams. Most research on this topic has been solely focused on longitudinal automation, however in real world applications lateral control is needed, even in purely straight paths. The purpose of this dissertation is thus to propose and analyze a combined lateral and longitudinal controller for vehicle platooning applications. Firstly, a longitudinal controller is evaluated in a vehicle following control strategy. Next, a lateral control structure is added to the previous controller and several both control strategies are discussed, vehicle following and path following, and their respective simulation results.